Upaya Perlindungan Pekerja Migran Indonesia Berdasarkan Uu Pmi: Studi Kasus Korban Di Kamboja - Fahmi Pamungkas DL, Muhammad (Jurnal sosial dan sains, 2025)
ecently, the public has been shocked by the phenomenon of Indonesian Migrant Workers who were victims of violence until they died in Cambodia. The reality of Indonesian society is important to see what is behind this phenomenon and how protection efforts are made by the Indonesian Government. In this study, researchers used the push and pull factor approach as an analytical knife in dissecting the phenomenon. The methodology used is Normative with a case approach. This research uses the theory of legal protection and the theory of legal certainty of protection and the value of legal certainty to understand the research topics discussed. The results of this study show that there is still a legal gap as evidenced by the high number of non-procedural departures of Indonesian migrant workers. Researchers provide recommendations related to handling this phenomenon as an effort for the Indonesian Government to protect and break the chain of violence that occurs against Indonesian Migrant Workers in Cambodia.